A decision-support system for safeguards information analysis. (13th June 2007) - Maschio, Isabella
The international nuclear proliferation control regime is facing the necessity to handle increasing amounts of information in order to assess nations' compliance with their safeguards commitments. The present paper proposes a Decision Support System (DSS) based on a fuzzy logic approach. The inbuilt information aggregation methodology is based on proliferation indicators as 'quanta of information' and develops within the framework of fuzzy sets as their computable counterpart. Both the reliability of the information sources and the relevance of the information are essential characteristics that are taken into account in the aggregation process. The decision-support system described in this work was presented at the IAEA Symposium on International Safeguards Addressing Verification Challenges, Vienna, Austria, 16-20 October 2006, and the fuzzy aggregation methodology at the Fuzzy Logic in Nuclear Science Conference (FLiNS06) in Genoa, Italy, 28-30 August 2006.